2021
DOI: 10.1007/s11096-021-01268-5
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and the challenges facing pharmacists during COVID-19: results of a national survey

Abstract: Background COVID-19 has impacted the psychological wellbeing of healthcare workers and has forced pharmacists to adapt their services. Objective To measure burnout and describe the work and psychosocial factors affecting pharmacists during COVID-19, and to compare males and females. Setting An online survey was distributed to a convenience sample of pharmacists practicing in any setting in Australia during April and June 2020. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 60 publications
2
76
3
Order By: Relevance
“…104 Regarding sex differences, women healthcare personnel (including nurses, physicians, pharmacists, and other healthcare workers) have had higher emotional exhaustion, 104,112,114,117,[119][120][121] whereas males report higher depersonalization. 112,114,117,121,122 Regarding gender, a study of U.S. anesthetists in March 2020 found that those who identify as LGBTQ2S+ experienced greater burnout. 123 Similarly, burnout was greater in individuals identifying as having non-binary gender in a nationwide U.S. survey of diverse healthcare professions between May and October 2020.…”
Section: Nurses and Workers In Intensive Care And Emergency Department Settings Are At Higher Risk Of Burnoutmentioning
confidence: 99%
“…104 Regarding sex differences, women healthcare personnel (including nurses, physicians, pharmacists, and other healthcare workers) have had higher emotional exhaustion, 104,112,114,117,[119][120][121] whereas males report higher depersonalization. 112,114,117,121,122 Regarding gender, a study of U.S. anesthetists in March 2020 found that those who identify as LGBTQ2S+ experienced greater burnout. 123 Similarly, burnout was greater in individuals identifying as having non-binary gender in a nationwide U.S. survey of diverse healthcare professions between May and October 2020.…”
Section: Nurses and Workers In Intensive Care And Emergency Department Settings Are At Higher Risk Of Burnoutmentioning
confidence: 99%
“… 57 A recent study demonstrated that Australian pharmacists are affected by burnout particularly due to working extra hours, challenges to medication supply management, and unsociable behaviours exhibited by pharmacy cutomers. 58 Support services to improve psychological wellbeing is crucial as the impact of COVID-19 in mental health of pharmacists could be extremely detrimental.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 Pharmacists have reported burnout during COVID-19 as well as changes to their work including increased workload, working overtime, and dealing with medication supply issues. 9 Many pharmacists across the health sector have had to adapt to support the changing needs of patients and the healthcare system. The accessibility of community pharmacists has been crucial to ensuring adequate healthcare provision, often being the first contact of care for patients with mild ailments, particularly as telehealth replaced many non-critical face-to-face healthcare consultations.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Pharmacists in all practice settings have been required to adapt to rapidly changing and inconsistent advice, which has affected their psychological wellbeing with increased rates of burnout reported. 9 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation